2004
DOI: 10.1097/01.ju.0000145527.08591.27
|View full text |Cite
|
Sign up to set email alerts
|

Spermatic Cord Torsion With Preserved Testis Perfusion: Initial Anatomical Observations

Abstract: Testis perfusion can be maintained for a prolonged period in the presence of testicular torsion. Anatomical variability may account for differences in the duration of viability of the torsed testis. A high index of suspicion must be maintained to avoid missing the diagnosis of testicular torsion in these challenging cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 14 publications
0
39
0
Order By: Relevance
“…Moreover, Bentley et al [15] concluded that boys with testicular torsion who have specific anatomical characteristics such as unusually thick spermatic cord preserve intratesticular flow in the affected testis and are at high risk of misleading findings of torsion if the diagnosis is based solely on color Doppler sonography [15].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Bentley et al [15] concluded that boys with testicular torsion who have specific anatomical characteristics such as unusually thick spermatic cord preserve intratesticular flow in the affected testis and are at high risk of misleading findings of torsion if the diagnosis is based solely on color Doppler sonography [15].…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe any statistically significant difference in the degree of torsion between patients undergoing orchidopexy and those requiring orchidectomy. These anatomical observations can also explain the cases with preserved flow on CDU in spite of the presence of torsion [10]. Initial studies interpreted these cases as false positives [11], but this may not be correct.…”
Section: Discussionmentioning
confidence: 98%
“…Three variables could account for the different effects of torsion on testicular outcome, the degree of torsion, the thickness of the cord and the degree of bell-clapper deformity (attachment of the mesorchium on the testicle) [10]. The latter determines whether torsion will occur, the possible degree of twisting and the likelihood of spontaneous detorsion.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is confirmed if increased flow is observed on color Doppler ultrasound. Patients with spermatic cord torsion with preserved testicular perfusion are at particular risk for missed torsion when the diagnosis of torsion is based solely on color flow Doppler findings [1].…”
Section: Discussionmentioning
confidence: 99%